PENGARUH RESPON, SEJARAH, REPUTASI, DAN ATRIBUSI KRISIS TERHADAP REPUTASI PARTAI POLITIK - Ardian Sopa (JURNAL BUANA INFORMATIKA CBI, 2016)
Abstract This study analyzed the impact of variable Crisis Respon Strategi, Crisis History, and Prior Relation Reputation toward Political Party Reputation. Sample of 200 respondents with age above 17 in Jakarta. The sampling method used purposive sampling technic. The sampling method used is Non-Probability Sampling. Data anaylis method used are SEM (Structural Equation Modelling). Findings of this research is the Crisis Respon Strategi, Crisis History, Prior Relation Reputation, and Atribution Responsibility, effect significan to Reputation. Keywords: Management, SCCT, Crisis Respon Strategi, Public Relations, Reputation